PENGARUH LIKUDITAS (CASH RATIO) DAN LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS ASET (ROA) PADA SEKTOR PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2008 - 2012 - Putri, Andiena Nindya; Triayarti, Nyoman . (E-Jurnal Manajemen; Vol 2 No 10 (2013), 2013)
ABSTRACT This study aims to discover relationship between cash ratio dan loan to deposit ratio influenced asset profitability on listed banking sector in indonesia stock exchange period 2008 - 2012. this study based on 21 banks financial report published by indonesia stock exchange since 2008 untill 2012 and multi regression analysis method has been used in this study. the researcher discovered that 1) cash ratio has significant impact and negatively influenced on asset profitability. 2) Loan to Deposit ratio negatively influenced on asset profitability. the lack of this research are 1) this research has autocorelation problem, similar research in the future supposed to use anallysis regresion of logaritma to solve the autocorrelation problem that might exist in the similar research in futur. 2) the similar research supposed to add few more independent variable which it be able to provide more variation
Keywords: Loan to Deposit Ratio, Cash Ratio, Asset Profitability